Evaluation of substituted triazol-1-yl-pyrimidines as inhibitors of Bacillus anthracis acetohydroxyacid synthase - Gedi, Vinayakumar; Jayaraman, Kumaresan; Kalme, Satish; Park, Hye-Yeon; Park, Hae-Chul; La, Im-Joung; Hahn, Hoh-Gyu; Yoon, Moon-Young (ELSEVIER SCIENCE BV, 2010)
Acetohydroxyacid synthase (AHAS), a potential target for antimicrobial agents, catalyzes the first common step in the biosynthesis of the branched-chain amino acids. The genes of both catalytic and regulatory subunits of AHAS from Bacillus anthracis (Bantx), a causative agent of anthrax, were cloned, overexpressed in Escherichia coli, and purified to homogeneity. To develop novel anti-anthracis drugs that inhibit AHAS, a chemical library was screened, and four chemicals, AVS2087, AVS2093, AVS2387, and AVS2236, were identified as potent inhibitors of catalytic subunit with IC50 values of 1.0 +/- 0.02, 1.0 +/- 0.04, 2.1 +/- 0.12, and 2.0 +/- 0.08 mu M, respectively. Further, these four chemicals also showed strong inhibition against reconstituted AHAS with IC50 values of 0.05 +/- 0.002, 0.153 +/- 0.004, 1.30 +/- 0.10, and 1.29 +/- 0.40 mu M, respectively. The basic scaffold of the AVS group consists of 1-pyrimidine-2-yl-1H-[1,2,4]triazole-3-sulfonamide. The potent inhibitor, AVS2093 showed the lowest binding energy, -8.52 kcal/mol and formed a single hydrogen bond with a distance of 1.973. As the need for novel antibiotic classes to combat bacterial drug resistance increases, the screening of new compounds that act against Bantx-AHAS shows that AHAS is a good target for new anti-anthracis drugs. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: ESCHERICHIA-COLI; BIOSYNTHETIC-PATHWAY; POTENT INHIBITORS; AMINO-ACIDS; SUBUNITS; IDENTIFICATION; RECONSTITUTION; TUBERCULOSIS; ACETOLACTATE; BINDING